REVIEW ON PHYTOEXTRACTION OF NICKEL IN THE CONTEXT OF PLANT-METAL INTERACTION - V. SATHYA; S. MAHIMAIRAJA (The Bioscan, 2018)
Metal pollutants can be produced through industrial processes such as mining, refining, and electroplating.Due to continuous irrigation of sewage water in agricultural field, application of sewage sludge to the crops, indiscriminate disposal of electroplating industry effluent and some fertilizer usage lead to the Ni contamination in soil. Presently phytoremediation is a popular technology which deals with the rehabilitation of metal contaminated sites using plants.In phytoremediation, phytoextraction is the major mechanism which absorbs metals from the soil and accumulated in plant biomass. The major criteria for selecting plant species plant species for phytoextraction are hyperaccumulating, fast growing species with high biomass. Physico-chemical and biological processes of soil systems also significantlyaffect themetal bioavailability. The primary soil factors controlling bioavailability are soil pH, cation or anion exchange capacity, clay content, and soil organic matter.For chemically-assisted phytoextraction, the dynamics of metal chelates in the rhizosphere need to be examined, either to overcome the risks associated with low degradability of synthetic chelators, or to optimize the use of more biodegradable compounds. A complete understanding of plant metal tolerance will be essential to develop strategies to genetically enhance the metal accumulation ability of plants.